2007
DOI: 10.1128/aem.02223-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fingerprinting of the Fecal Microbiota of Children Raised According to Different Lifestyles

Abstract: In this population-based study, 90 children from three European countries were examined to determine the impact of lifestyle on the fecal microbiota. The study was designed to assess the impact of two extreme lifestyles that we hypothesized could impact the microbial composition in the gut: i.e., an anthroposophic lifestyle (restricted use of antibiotics, greater consumption of fermented vegetables, etc.) versus living on a farm (greater consumption of farm milk, contact with animals, etc.). In previous studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 37 publications
6
75
1
3
Order By: Relevance
“…The search for a causative disease agent is complicated by the great individuality of the gut microbiota with little overlap between individuals (Zoetendal et al, 1998;Eckburg et al, 2005;Dicksved et al, 2007). However, previous findings have shown that there is a high similarity in the composition of the fecal microbial communities in monozygotic twins (Van de Merwe et al, 1983;Zoetendal et al, 2001;Stewart et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The search for a causative disease agent is complicated by the great individuality of the gut microbiota with little overlap between individuals (Zoetendal et al, 1998;Eckburg et al, 2005;Dicksved et al, 2007). However, previous findings have shown that there is a high similarity in the composition of the fecal microbial communities in monozygotic twins (Van de Merwe et al, 1983;Zoetendal et al, 2001;Stewart et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…Untangling the possible contribution of microorganisms to CD has been complicated by the large variability in the composition of the gut microbiota in humans. Basically, each human has an individual fecal microbial fingerprint (Zoetendal et al, 1998;Eckburg et al, 2005;Dicksved et al, 2007). However, the study of monozygotic twins basically eliminates the variable of host genetics, except for potential epigenetic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of the gut microbiota is relatively simple in infants but becomes more complex with increasing age, reaching a high degree of complexity in adults (Fanaro et al, 2003). Lifestyle factors (Dicksved et al, 2007) and diet (Flint et al, 2007;Ley et al, 2005Ley et al, , 2006 can also affect the diversity and composition of the gut microbiota. Interestingly, the relative proportions of the two most dominant bacterial phyla i.e.…”
Section: The Normal Human Gut Microbiota Ecosystemmentioning
confidence: 99%
“…Bacteroidetes and Firmicutes, were found to be correlated with obesity in mice and humans, respectively (Ley et al, 2005(Ley et al, , 2006, but a study by Duncan et al (2008) did not see this same correlation in obese and lean humans. Molecular analyses have also revealed that the composition of the human intestinal microbiota is host-specific (Dicksved et al, 2007;Jernberg et al, 2007) and relatively stable over time (Jernberg et al, 2007;Zoetendal et al, 1998). Recent metagenome sequencing data of 124 individuals suggest the existence of a common core human gut microbiome (Qin et al, 2010), but this core may exist more at the level of shared functional genes rather than shared taxa (Turnbaugh et al, 2007(Turnbaugh et al, , 2009).…”
Section: The Normal Human Gut Microbiota Ecosystemmentioning
confidence: 99%